Predator disease out‐break modulates top‐down, bottom‐up and climatic effects on herbivore population dynamics - Christopher C. Wilmers; Eric Post; Rolf O. Peterson; John A. Vucetich (Ecology Letters, 2006)
Human‐introduced disease and climatic change are increasingly perturbing natural ecosystems worldwide, but scientists know very little about how they interact to affect ecological dynamics. An outbreak of canine parvovirus (CPV) in the wolf population on Isle Royale allowed us to test the transient effects of an introduced pathogen and global climatic variation on the dynamics of a three‐level food chain. Following the introduction of CPV, wolf numbers plummeted, precipitating a switch from top‐down to bottom‐up regulation of the moose population; consequently, the influence of climate on moose population growth rate doubled. This demonstrates that synergistic interactions between pathogens and climate can lead to shifts in trophic control, and suggests that predators in this system may play an important role in dampening the effects of climate change on the dynamics of their prey.